St. King Ladislaus and the Council of Szabolcs (1092) - Szuromi, Szabolcs (Saeculum Christianum. Pismo Historyczne, 2019)
The present article examines the council of Szabolcs (1092) on the political, legal and ecclesiastical field. Firstly, the conciliar and canonical disciplinary background in Hungary is explained in order to show in the next part of the paper the importance, proceeding and provisions of the council of Szabolcs. Then, the precise survey of proceeding and provisions of the council is made with analysis of the content of the chapters and their textual correlation. In the conclusion is stressed that the council’s chapters standing close to the Eastern discipline are derived from universal canonical collections, and that the above-mentioned council should be regarded as first step in the longer process of reception of the Gregory VII’s canonical reform.